Traditional and Hybrid Access Control Models: A Detailed Survey. (7th February 2022) - Aftab, Muhammad Umar; Hamza, Ali; Oluwasanmi, Ariyo; Nie, Xuyun; Sarfraz, Muhammad Shahzad; Shehzad, Danish; Qin, Zhiguang; Rafiq, Ammar
Abstract : Access control mechanisms define the level of access to the resources among specified users. It distinguishes the users as authorized or unauthorized based on appropriate policies. Several traditional and hybrid access control models have been proposed in previous researches over the last few decades. In this study, we provide a detailed survey of access control models and compare the traditional and hybrid access control models based on their access control criteria. This survey focuses on the growing literature of access control models and summarizes it through comparative analysis, identifying limitations and illustrating the advantages of both traditional and hybrid models. This study will help the researchers to get a deep understanding of the traditional and hybrid access control models.